Oral delivery of Bacillus subtilis spores expressing grass carp reovirus VP4 protein produces protection against grass carp reovirus infection. Issue 84 (January 2019) - Jiang, Hongye; Bian, Qing; Zeng, Weiwei; Ren, Pengli; Sun, Hengchang; Lin, Zhipeng; Tang, Zeli; Zhou, Xinyi; Wang, Qing; Wang, Yingying; Wang, Yensheng; Wu, Mei X.; et al.
Abstract: Grass carp ( Ctenopharyngodon idellus ) hemorrhagic disease (GCHD), caused by grass carp reovirus (GCRV), has given rise to an enormous loss in grass carp industry during the past years. Up to date, vaccination remained to be the most effective way to protect grass carp from GCHD. Oral vaccination is of major interest due to its advantages of noninvasive, time-saving, and easily-operated. The introduction of oral vaccination has profound impact on aquaculture industry because of its feasibility of extensive application for fish in various size and age. However, the main challenge in developing oral vaccine is that antigens are easily degraded and are easy to induce tolerance. Bacillus subtilis ( B. subtilis ) spores would be an ideal oral vaccine delivery system for their robust specialty, gene operability, safety and adjuvant property. VP4 protein is the major outer capsid protein encoded by GCRV segment 6 (S6), which plays an important role in viral invasion and replication. In this study, we used B. subtilis spores as the oral delivery system and successfully constructed the B. subtilis CotC-VP4 recombinant spores (CotC-VP4 spores) to evaluate its protective efficacy in grass carp. Grass carp orally immunized with CotC-VP4 spores showed a survival rate of 57% and the relative percent survival (RPS) of 47% after the viral challenge. Further, the specific IgM levels in serum and the specific IgZ levels in intestinal mucus were significantly higher in the CotC-VP4 group than those in the Naive group. The immune-related genes including three innate immune-related genes (IL-4/13A, IL-4/13B, CSF1R), four adaptive immune-related genes (BAFF, CD4L, MHC-II, CD8), three inflammation-related genes (IL-1β, TNF-α, TGF-β) and interferon type I (IFN-I) related signaling pathway genes were significantly up-regulated in the CotC-VP4 group. The study demonstrated that the CotC-VP4 spores produced protection in grass carp against GCRV infection, and triggered both innate and adaptive immunity post oral immunization. This work highlighted that Bacillus subtilis spores were powerful platforms for oral vaccine delivery, and the combination of Bacillus subtilis spores with GCRV VP4 protein was a promising oral vaccine. Highlights: Successful construction of Bacillus subtilis spores expressing GCRV VP4 protein. Recombinant spores showed an effective protection against GCRV infection in fish. The viral load was reduced after immunization with recombinant spores in fish. Recombinant spores significantly triggered innate and adaptive immunity of fish.